AB0770 DESCRIBING A COHORT OF PATIENTS WITH PSORIATIC ARTHRITIS ACCORDING TO THE BODY MASS INDEX: EXPERIENCE IN A JOINT RHEUMATOLOGY-DERMATOLOGY CLINIC. (2nd June 2020) - García-Guillén, A.; Laiz, A.; Lopez-Ferrer, A.; Park, H.; Moya, P.; Magallares, B.; Castellví, I.; Millán Arciniegas, A. M.; Díaz-Torné, C.; Jeria, S.; Corominas, H.
Abstract : Background: Obesity is a predictor for the development of psoriatic arthritis (PsA) with a negative prognostic impact. Objectives: We aimed to describe and characterize patients with PsA according to the Body Mass Index (BMI) in a joint Rheumatology-Dermatology unit (PAIDER). Methods: We retrospectively reviewed patients diagnosed with PsA according to CASPAR criteria visited between May 2012 and May 2019 at the PAIDER clinic of our center. Data on demographic and anthropometric features, serologic findings, source of referral, cardiovascular risk factors and biological treatment were collected from clinical records. Patients were classified according to the WHO International Classification of nutritional status in normal weight (BMI 18.5-24.9 Kg/m2), overweight (BMI 25-29.9 Kg/m2) and obesity (BMI≥30 Kg/m2). A descriptive analysis was performed, and the differences between groups were evaluated using Chi2, T-Student and ANOVA tests. P-values <0.05 were accepted as significant. Results: During the study period 393 patients (50.6% women) with a mean age of 52.47 ± 13.21 years were evaluated. Baseline characteristics are shown in table 1. The mean BMI was 28.15 ± 5.87 kg/m 2 . 112 patients (32%) were overweight with a mean BMI of 27.46 ± 1.55 kg/m 2 and 118 patients (34%) were obese with a mean BMI of 34.42 ± 5.08 kg/m 2 . Of the obese patients, 80 (67.8%) had obesity grade 1, 28 (23.7%) grade 2 and 10 (8.5%) grade 3. Characteristics of the patients according to BMI categories are shown in Table 2. We observed that mean age was significantly higher in obese patients (p <0.001), as well as the prevalence of cardiovascular risk factors such as HBP (p <0.001), Diabetes (p <0.001), dyslipidemia (p = 0.001) and hyperuricemia (p = 0.004). Obese patients also received more biological therapy (p=0.032). A higher prevalence of HLA-B27 was observed in patients with normal weight (p=0.016). No differences were found according to BMI regarding gender and source of referral. Conclusion: - Almost 70% of patients with PsA visited in the PAIDER clinic of our center have a BMI above normal and more than a third of them are obese, mostly grade 1. - In our joint clinic there are no differences in BMI regarding the source of referral of the patients. - Patients with obesity are older, have more cardiovascular comorbidities and receive more biological treatment significantly, which increases the complexity of their management and worsens the prognosis. Disclosure of Interests: Andrea García-Guillén: None declared, Ana Laiz: None declared, Anna Lopez-Ferrer: None declared, HyeSang Park: None declared, Patricia Moya: None declared, Berta Magallares: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, Ana Milena Millán Arciniegas: None declared, Cesar Díaz-Torné: None declared, Sicylle Jeria: None declared, Hector Corominas: None declared